"If you can't tell, does it matter?" Westworld, the murder of the real, and 21st century schooling. Issue 2 (4th May 2019) - van Kessel, Cathryn; Kline, Kip
Abstract: The HBO series, Westworld, challenges our notions about what might be real. As such, the series provides a provoking platform for exploring an oft—neglected topic in contemporary education-the fetishization of technology and the murder of the real in Jean Baudrillard's sense. Current educational systems in Canada and the United States (and elsewhere) depend on an outmoded commitment to a world in which reality is assumed to be unobscured, but Westworld provides a provocative platform to renegotiate this assumption. There are consequences for a world in which simulacra have displaced the real, and these need to be explored in the context of education and beyond.